The evaluation of the specificity of the Acid Phosphatase test to identify semen - Conrad, Robyn (Department of Pathology, 2019)
The burden of sexual assault cases in South Africa is exceptionally high, and analysis of biological material in these cases may provide evidence towards a criminal investigation. These analyses include the identification of biological material to: (i) presumptively identify if semen may be present in order to guide downstream DNA profiling analysis to identify the alleged assailant; and (ii) confirm if semen was indeed present to provide evidence of ejaculation. The presumptive test used to detect the possible presence of semen is the Brentamine Fast Blue (FB) test, which detects the presence of acid phosphatase (AP) by a colour change reaction. AP is an enzyme which is present in human semen in high concentrations, but is also found in animal semen at lower concentrations. The current methods of presumptive testing cannot differentiate between animal and human semen. The specificity of the Brentamine FB test was therefore explored in this study, by subjecting semen from humans (n = 16), dogs (n = 13), horses (n = 5), ostriches (n = 9), and rams (n = 13) to this test; and measuring the enzyme kinetics using a novel method: UV-Vis spectrophotometry. Reaction kinetics showed a significant difference in the AP activity between humans and each of the four different animal species in this study (p < 0.001). Confirmatory testing was also performed using microscopy and morphological differences were seen between human and animal spermatozoa, with significant differences between human, ram, ostrich and dog semen (p < 0.05) but not horse semen (p > 0.05). This study demonstrates that enzyme kinetics holds potential to increase the specificity of presumptive testing for human semen, which could possibly be supplemented with microscopy-based confirmatory testing. These results are of value to forensic scientists who may be faced with questions regarding semen specificity in casework. Further, the baseline of semen morphometric dimensions generated for each species’ can aid in forensic investigations for comparison with evidential samples.